UJI EFIKASI EKSTRAK DAUN MAHONI (Swietenia mahagoni (L.) Jaqc.) TERHADAP HAMA ULAT GRAYAK (Spodoptera litura F.) DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Haryuni, Haryuni (JURNAL ILMIAH AGRINECA, 2014)
Indonesia has a huge, biological resources as a plant which can be used as a pesticide natural mahogany. The plant pesticide vegetable is pesticide, plant are based with the active ingredient  and  control of organism.  Obstacles in  cultivation of plant peanuts is Spodoptera litura F. pest attacks. Which result in a decrease in productivity and seeds being broken. The purpose  of  this  evaluation  to  understand  the  influence  of  extract mahogany  leaves  and intensity of  attacks  against  the  percentage  caterpillar  in plants peanut , to know intervals of time the application of appropriate to reduce the percentage of and intensity of pest attacks , and to know the influence of the interaction of concentration and intervals of time application extract mahogany  leaves.  This   research   in   a   random  complete   the   group   consisting   of   two factors.The first concentration extract leaves mahogany and the second factor intervals of time application  .But  the  research  referred  to  as  follows  1  )  the  f i r s t   ,  the  extract leaves mahogany (A) : A0: 0 % (control),  A1 : 8% , A2 : 10%, A3: 12% , 2) factors s e c o n d , the time interval application (B): B1: every day once upon 3 , B2 : every day once upon 5, B3 : every day once upon 7. Every treatment repeated 3 times. The results of the study show concentration extract  leaves  mahogany  to  reduce   caterpillar   grayak   pest    attacks       .Extract    leaves mahogany  with  intervals  of  time  the  application    had an influence on the percentage and intensity of pest  attacks caterpillar  and  influential on the parameter the    results    of   .The percentage  of  highest  attack  A0B3   38,05  %  the  lowest percentage A3B1  3,91 % as much as  . For  the  intensity of the  attack  highest A0B3 25,77 % and the lowest A3B1 13,76 % as much as .The results of fresh pods peanut the highest A3B1  (6,0608 t /ha) and the lowest A1B3 with the results of (0,5431 t /ha).